2016
DOI: 10.1515/cer-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Of Tourism – EU Ecolabel Standards Illustrated Using The Example Of Poland

Abstract: Tourism, as one of the biggest and fastest growing industries in the world, has an enormous impact on the achievements of the Europe 2020 growth strategy. The main factor influencing its effectiveness, based on achievement of strategy indicators, is tourist infrastructure, which is understood as hotel and restaurant facilities used by tourists coming to a particular area to meet their needs associated with passive and active tourism. To achieve the highest effectiveness in this regard, the European Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The authors preoccupied with studying the ecolabel implementation process [30][31][32][33][34] emphasized that the main motivation of tourism enterprises to obtain such a certification is the image delivered to customers-an environmentally friendly business. Studies on the impact of ecolabelling have focused on several directions: the advantages of ecolabelling for tourism companies, tourism industry, and tourists [35,36], the difficulties that companies face when trying to obtain such a certification, and the impact of holding an ecolabel on the consumers' decision [17,37]. There are also less investigated aspects, such as those regarding the real advantages that an ecolabel brings to tourism businesses, although the theoretical advantages are listed in several research works [35,38].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors preoccupied with studying the ecolabel implementation process [30][31][32][33][34] emphasized that the main motivation of tourism enterprises to obtain such a certification is the image delivered to customers-an environmentally friendly business. Studies on the impact of ecolabelling have focused on several directions: the advantages of ecolabelling for tourism companies, tourism industry, and tourists [35,36], the difficulties that companies face when trying to obtain such a certification, and the impact of holding an ecolabel on the consumers' decision [17,37]. There are also less investigated aspects, such as those regarding the real advantages that an ecolabel brings to tourism businesses, although the theoretical advantages are listed in several research works [35,38].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Other aspects that are even less studied are represented by the opinions of the managers from the hospitality industry regarding the necessity to obtain an ecolabel. Covering this research area are the works of Dziuba [36], Ryglova [39], and Duglio et al [40].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Other indicators of environmental performance include the award of an eco-label. Eco-label management today is an example of innovative hotel management [14]. Environmental policy implements environmental protection, waste policy, recycling, above all, the integration of employees themselves into environmental thinking [11].…”
Section: Methods and Databasementioning
confidence: 99%
“…Thus, the statistics for 2016 showed that most licenses for France and Italy fall in the Tourist Accommodation category, with 287 and 186, respectively. The success of this category in those countries could be attributed to their importance in the top ten world tourist destinations (UNWTO 2016) and the multiple economic benefits based on the eco-efficiency improvements and cost savings achieved by the EU Flower certification process (Dziuba 2016). Also in 2016, in Germany, the licenses are more distributed over different kinds of products, although a significant amount belongs to specific subcategories like All-purpose & Sanitary Cleaners (47), Lubricants (48), and Tissue Paper (40).…”
Section: European Status Of Eu Flowermentioning
confidence: 99%